Periodontal health and use of oral health services: a comparison of Germans and two migrant groups - Hagenfeld, Daniel; Zimmermann, Heiko; Korb, Katja; Sayed, Nihad el; Greiser, Karin Halina; Kim, Ti-Sun; Becher, Heiko (International journal of environmental research and public health, 2019)
A cross-sectional study was performed with 251 individuals, consisting of 127 Germans, 68 migrants from Turkey, and 56 resettlers (migrants from the former Soviet Union with German ancestors) to compare periodontal health status, with a special focus on associations with lifestyle and anthropometric factors, and use of dental health services. Maximal pocket depth was used as a clinical surrogate marker for periodontitis. Other variables were obtained by questionnaires administered by a Turkish or Russian interpreter. The age- and sex-adjusted prevalence of periodontitis was significantly higher in Turks (odds ratio (OR) 2.84, 95% CI = 1.53-5.26) and slightly higher in resettlers (OR = 1.33, 95% CI = 0.71-2.49). These differences are partly explained by a differential distribution of known risk factors for periodontitis. A full model showed a higher prevalence of maximal pocket depth above 5 mm in Turks (OR = 1.97, 95% CI = 0.99-3.92). Use of oral health services was significantly lower in the two migrant groups. Individuals who reported regular visits to a dentist had significantly less periodontitis, independent of migrant status. A reasonable conclusion is that, since oral health causes major chronic diseases and has a major effect on total health system expenditures, public health efforts both generally and specifically focused on migrant groups are warranted.